How Difficult Is It for Managers to Predict Their Future Business Development? A New Measure of Perceived Business Uncertainty - Stefan Lautenbacher; Stefan Sauer; Klaus Wohlrabe (CESifo Forum, 2021)
This article introduces the ifo Business Uncertainty, a measure of how difficult it is for managers to predict the future business development of their firm. The indicator is based on a new monthly question in a representative survey of the German economy, the ifo Business Survey. It captures the perceived uncertainty of managers, because it could affect their investment and hiring decisions, and thus the business cycle. We show that our new measure of perceived un-certainty increased sharply at the beginning of the Covid-19 crisis. Since then, it has decreased somewhat, but it remains at an elevated level. Moreover, we compare the ifo Business Uncertainty to a second indicator of firms' subjective uncertainty and find that they are almost perfectly aligned. Last, we show that the relationship of the ifo Business Uncertainty with the ifo Business Climate Index is strongly negative.
Keywords: 330